LASKAR HEBAT : LANSIA KARAME HIDUP SEHAT BAHAGIA DI HARI TUA: GREAT LASKAR : KARAME ELDERLY LIFE HEALTHY HAPPY IN OLD DAYS - Bayu Dwisetyo; Irma M Yahya; Agust Arthur Laya (Jurnal Pengabdian Ilmu Kesehatan, 2022)
In the era of the COVID-19 pandemic, it is hope that the elderly can maintain their health status. However, it is found that there is no supporting health facilities to improve the health of the elderly. This community service activity aims to make the elderly healthy both physically and spiritually through several activities, like gymnastics, elderly independence checks, health checks and education about healthy and great elderly and carried out in Karame, Singkil, Manado. Through this activity, it is seen the level of independence before and after exercise and how the health of the elderly during the pandemic and increases the knowledge of how to become healthy and great elderly. This activity has a positive impact for the elderly to pay more attention about health status.